Numerical Study on Failure Mechanisms of Shaft Wall Consisting of Steel Plate and Concrete under the Effects of Explosion - Yanjun Qi; Linming Dou; Zhaoxing Dong; Bo Meng (Advances in Civil Engineering)
To enhance the antidynamic and static load resistance of reinforced concrete structures, the measure of covering steel plates on the inner surface of concrete structures arises, which has been rapidly developed and applied in civil engineering and other fields and has achieved a good performance. A new shaft wall structure consisting of steel plate reinforced concrete has been widely used in shaft of deep mining. In order to investigate the stability and obtain the optimum structure parameters of the new shaft structure, the numerical software of LS-DYNA was used to analyze the influences of different factors, including the explosive payload, steel plate thickness, concrete strength grade, and the included joint angle between two plates, on the stability of steel plate reinforced concrete structures. After the verification of the accuracy of numerical simulation results, 23 simulation schemes were proposed and numerically calculated. For all the tests, the principal tensile stress and particle vibration velocity were, respectively, chosen as the failure criteria to evaluate the impacts of those four factors. The results indicate that a quadratic function can be well used to describe the relationships between each factor and both the principal tensile stress and particle vibration velocity. Based on the results, the optimum structure parameters were finally determined, which are suggested as 250 kg, 15 mm, C85, and 40° for the explosive payload, steel plate thickness, concrete strength grade, and joint angle, respectively. The research results can provide a certain theoretical basis and design guidance for solving the problem of water leakage of single-layer shaft wall structures.